Oral Curcumin With Piperine as Adjuvant Therapy for the Treatment of COVID-19: A Randomized Clinical Trial - Pawar, Kirti S; Mastud, Rahul N; Pawar, Satheesh K; Pawar, Samragni S; Bhoite, Rahul R; Bhoite, Ramesh R; Kulkarni, Meenal V; Deshpande, Aditi R (Frontiers in Pharmacology, 2021)
Background: Coronavirus disease-2019 (COVID-19) has a wide range of pathophysiological effects. Curcumin, an active constituent of Curcuma longa (turmeric), has several properties, including anti-inflammatory, antioxidant, antiviral, anti-thrombotic, and anti-proliferative effects, which make it a promising candidate for the treatment of COVID-19. Objective: We aimed to determine the effects of curcumin administered with bioperine (to optimize absorption) in patients with COVID-19 in a double-blind, randomized, controlled trial at a 30-bed dedicated COVID Health Center (DCHC) in Maharashtra, India. Methods: In addition to conventional COVID-19 treatment, patients in the control group received a dose of probiotic twice a day, and patients in the study group received curcumin (525 mg) with bioperine (2.5 mg) in tablet form twice a day. The effects of curcumin/bioperine treatment on primary and secondary outcomes were assessed for the duration of hospitalization. Results: Patients with mild, moderate, and severe symptoms who received curcumin/bioperine treatment showed early symptomatic recovery, less deterioration, fewer red flag signs, better ability to maintain oxygen saturation above 94% on room air, and better clinical outcomes compared to patients of the control group. Further, curcumin/bioperine treatment appeared to reduce duration of hospitalization in patients with moderate to severe symptoms, and fewer deaths were observed in the curcumin/bioperine treatment group. Conclusion: Administration of oral curcumin with bioperine as an adjuvant therapy in COVID-19 treatment could substantially reduce morbidity and mortality, and ease the logistical and supply-related burdens on the healthcare system. Curcumin can be a safe and natural therapeutic option to prevent Post-Covid thromboembolic events. Trial Registration: This trial is registered at clinicaltrials.gov (http://www.clinicaltrials.gov) with the identifier CTRI/2020/05/025482.